Sexuality and the law - D'Agostino, Francesco (Medicina e Morale, 1997)
The author first indicates the limits of a merely phenomenological and functionalist conception of sexuality. It is a conception which underestimates sexuality in its deepest aspects and in the fullest understanding of man himself. An "integrated" approach to sexuality is therefore necessary and it is considered a question of truth. After illustrating the anthropogenetic process, again with reference to sexuality, the way Lacan explained it, the author claims that there is a need for a law on human sexuality. In fact to consider sexuality as a merely subjective law, with the expected "privatization" of sexuality, is more an ideological postulate than an authentic hermeneutic possibility. Actually the law, which is constantly called on to regulate relationships, can not but provide regulations about the practice of sexuality and require than they be observed, because it is in this practice than the balance of the interpersonal relationship manifest itself most. None the less one must bear in mind that the lawyer uses a criterion, rather than a series of formal rules, which corresponds to the general criterion which governs the legal world, that is, of relationship, understood as the balance within the difference. Sexuality, rather than any other dimension, is in fact constantly aware of the presence of the law, of this insistent memory of the presence, next to the "ego", of the other person, and of his rights and of what is due to him.